2008 IEEE Nuclear Science Symposium Conference Record 2008
DOI: 10.1109/nssmic.2008.4775228
|View full text |Cite
|
Sign up to set email alerts
|

4π coded aperture imaging using 3d position-sensitive CdZnTe detectors

Abstract: Abstraet-3D position sensitive CdZnTe semiconductor detectors have demonstrated 4n Compton imaging ability and excellent energy resolution at room-temperature operation. An array of such detectors would provide unique detection capabilities. However, Compton imaging is challenging at low energies due to the small Compton-scatter cross-section. This work extends the imaging capabilities to lower energies by utilizing multiple coded aperture masks.Each coded aperture mask is applied to one of five sides of a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Compton cameras can achieve up to 4π-view FOV with a high detection sensitivity [ 6 ]. However, they are usually not capable of imaging low-energy sources (<200 keV) due to the low interaction probability [ 7 ]. Several recent works also equip Compton cameras with a metal coded-aperture collimator [ 8 ] to image low-energy isotopes in a reduced FOV, or with an active pinhole detector layer [ 9 ], or a coded-aperture shape detector layer [ 10 ] to both expand the image FOV and energy range, but at the expense of increased system design complexity, device weight, and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Compton cameras can achieve up to 4π-view FOV with a high detection sensitivity [ 6 ]. However, they are usually not capable of imaging low-energy sources (<200 keV) due to the low interaction probability [ 7 ]. Several recent works also equip Compton cameras with a metal coded-aperture collimator [ 8 ] to image low-energy isotopes in a reduced FOV, or with an active pinhole detector layer [ 9 ], or a coded-aperture shape detector layer [ 10 ] to both expand the image FOV and energy range, but at the expense of increased system design complexity, device weight, and cost.…”
Section: Introductionmentioning
confidence: 99%
“…SORIS (Zelakiewicz et al, 2011) employed a nonplanar mask to obtain a view of about 180 , but this suffered from a relatively low angular resolution. Kaye et al (2008) demonstrated near-4p gamma-ray imaging by using multiple three-dimensional (3D) position-sensitive pixilated detectors by combing both Compton and coded aperture imaging techniques; however, the detection efficiency is very poor.…”
Section: Introductionmentioning
confidence: 99%